2019
DOI: 10.1007/s10354-019-00707-3
|View full text |Cite
|
Sign up to set email alerts
|

Apps in der Sekundärprävention nach Schlaganfall

Abstract: Zusammenfassung Laut der INTERSTROKE Studie werden etwa 90 % des Risikos für einen ischämischen Schlaganfall durch beeinflussbare Risikofaktoren (z. B. Bluthochdruck, Übergewicht, Rauchen) bedingt. Durch eine Verringerung dieser Faktoren könnte das Schlaganfallrisiko deutlich gesenkt werden. Um die Effektivität von Smartphone Apps zur Sekundärprävention nach Schlaganfall in Bezug auf beeinflussbare Risikofaktoren und die Einstellung von Zusatzmaterial online Zusätzliche Informationen sind in der Online-Version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 53 publications
(48 reference statements)
0
4
0
2
Order By: Relevance
“…Studies conducted on numerous diseases have already confirmed the potential of apps to support self-management and be instrumental in the treatment plan [26][27][28]. An increasing number of studies are focusing on the use of asthma apps [4,[29][30][31][32].…”
Section: Renderxmentioning
confidence: 99%
“…Studies conducted on numerous diseases have already confirmed the potential of apps to support self-management and be instrumental in the treatment plan [26][27][28]. An increasing number of studies are focusing on the use of asthma apps [4,[29][30][31][32].…”
Section: Renderxmentioning
confidence: 99%
“…Digital tools for managing acute stroke care and monitoring post–acute-stroke care for patients discharged to community are rapidly being developed and integrated into care systems 25,26. Embedded within many international stroke guidelines are recommendations for the digitalization of elements of stroke patient care 27.…”
Section: Research Opportunitiesmentioning
confidence: 99%
“…23,24 Digital tools for managing acute stroke care and monitoring post-acute-stroke care for patients discharged to community are rapidly being developed and integrated into care systems. 25,26 Embedded within many international stroke guidelines are recommendations for the digitalization of elements of stroke patient care. 27 The intent of digital health technology is to improve service quality, efficiency, and equity in access to care and includes nurse-led stroke research.…”
Section: Research Opportunitiesmentioning
confidence: 99%
“…Anti-Stress-Apps) zur Förderung der psychischen Gesundheit sind auf mobilen Endgeräten verfügbar und können autonom zeit- und ortsunabhängig genutzt werden und dienen Studierenden zum Selbstmanagement belastender Alltagssituationen [ 21 ]. Dabei wird zwischen primären Anti-Stress-Apps, die direkt die Erkrankungen oder spezifische Symptome fokussieren sowie sekundären Anti-Stress-Apps, die sich mehr auf die Reduktion von Risikofaktoren konzentrieren, unterschieden [ 7 ]. Obwohl das Interesse für die Nutzung von Anti-Stress-Apps vorhanden ist, nehmen die Studierenden diese nur begrenzt in Anspruch: Die Befragungen von Kern et al.…”
Section: Hintergrundunclassified